PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. ARIER REKAYASA NUSANTARA MEDAN - Veramika Sembiring; Johari sitompul; Evi Rosalina Hutabarat (JURNAL GLOBAL MANAJEMEN, 2020)
This study aims at determining whether motivation and compensation affect on employee performance at PT. Arier Rekayasa Nusantara. The hypothesis in this study is "Motivation and compensation have a positive effect on employee performance at PT. Arier Rekayasa Nusantara”. The data collection method used by the writer is Field Research. The sample in this study amounted to 30 employees. This study uses a multiple linear regression analysis model. The results of this study indicate a multiple linear regression equation where Y = 5.532 + 0.655X1 + 0.288X2, which means motivation and compensation have a positive effect on employee performance. The results of the coefficient of determination test on R square of 0.635 means 63.5% Motivation variable can be explained by the Employee Compensation and Performance variables while the remaining 32.5% can be explained by other factors not examined by this study. The results on the simultaneous test (Test F) can be seen that the value of Fcount 23.516 > F table 3.34. This determines that the independent variables consisting of independent variables motivation and compensation simultaneously have a positive and significant effect on the dependent variable, namely employee performance at PT. Arier Rekayasa Nusantara.